Correlates of bacterial ulcers and acute HSV-2 infection among men with genital ulcer disease in South Africa: age, recent sexual behaviours, and HIV. Issue 2 (9th June 2016) - Leichliter, Jami S.; Lewis, David A.; Paz-Bailey, Gabriela
Abstract : Data from baseline surveys and STI/HIV laboratory tests (n=615 men) were used to examine correlates of bacterial ulcers ( Treponema pallidum, Haemophilus ducreyi, or Chlamydia trachomatis L1-L3 detected in ulcers) and acute HSV-2 ulcers (HSV-2 positive ulcer specimen, HSV-2 sero-negative, and negative for bacterial pathogens) versus recurrent HSV-2 ulcers (sero-positive), separately. Men with bacterial ulcers had larger ulcers compared to men with recurrent HSV-2 ulcers, but were less likely to be HIV-positive; whereas, men with acute HSV-2 ulcers were younger with fewer partners. Acute HIV was higher among men with bacterial and acute HSV-2 ulcers; however, this difference was not statistically significant.